2019
DOI: 10.1038/s41565-018-0344-3
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoglobulin deposition on biomolecule corona determines complement opsonization efficiency of preclinical and clinical nanoparticles

Abstract: Deposition of complement factors (opsonisation) on nanoparticles may promote clearance from the blood by macrophages and trigger proinflammatory responses, but the mechanisms regulating the efficiency of complement activation are poorly understood. We previously demonstrated that opsonisation of superparamagnetic iron oxide nanoworms (SPIO NWs) with the third complement protein (C3) was dependent on the biomolecule corona. Here we show that natural antibodies play a critical role in C3 opsonisation of SPIO NWs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
233
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(237 citation statements)
references
References 49 publications
4
233
0
Order By: Relevance
“…In another study, it was shown that clinical and preclinical NPs are recognized by “natural” pre-existing antibodies and that labeling of NP-bound IgG by C3b/iC3b opsonins is crucial for an effective capture by phagocytes ( 69 ). The use of FcR-negative or overexpressing cell lines also indirectly suggested that NP-bound antibodies mediate cell interaction with phagocytes ( 41 , 70 ).…”
Section: Influence On Np-cell Interactions Of Specific Np-bound Protementioning
confidence: 99%
“…In another study, it was shown that clinical and preclinical NPs are recognized by “natural” pre-existing antibodies and that labeling of NP-bound IgG by C3b/iC3b opsonins is crucial for an effective capture by phagocytes ( 69 ). The use of FcR-negative or overexpressing cell lines also indirectly suggested that NP-bound antibodies mediate cell interaction with phagocytes ( 41 , 70 ).…”
Section: Influence On Np-cell Interactions Of Specific Np-bound Protementioning
confidence: 99%
“…Upon exposure to biofluids, the NPs acquire a "protein corona" due to the adherence of host proteins on the NPs surface. The composition of the corona is dependent on the types of nanoparticles and the biological sources [1][2][3] , and considered to provide the NPs with a "biological" identity 4 that affects stability, circulation time, and cellular uptake/interactions, and therefore has a strong impact on the functional role for the NPs [5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Indeed, one proposed mechanism of ENM-induced complement activation and C3 opsonization is attributed to subsequent conformational changes of ENM-adsorbed biomacromolecules (i.e., exposing antigenic epitopes) (46). Further, it has been recently shown that natural antibodies play a key role in ENM-induced complement opsonization (47). Importantly, such mechanisms appears to be universal to multiple preclinical and clinical nanomedicines (47).…”
Section: Interaction With and Activation Of The Complement Systemmentioning
confidence: 99%
“…Further, it has been recently shown that natural antibodies play a key role in ENM-induced complement opsonization (47). Importantly, such mechanisms appears to be universal to multiple preclinical and clinical nanomedicines (47). Taken together, due to ENM size and physicochemical properties (e.g., shape, surface charge, topography, hydrophobicity, etc.…”
Section: Interaction With and Activation Of The Complement Systemmentioning
confidence: 99%